2010
DOI: 10.3109/09637480903455971
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-preventing attributes of probiotics: an update

Abstract: Cancer is a serious global public health problem. Cancer incidence and mortality have been steadily rising throughout the past century in most places of the world. There are several epidemiological evidences that support a protective role of probiotics against cancer. Lactic acid bacteria and their probioactive cellular substances exert many beneficial effects in the gastrointestinal tract, and also release various enzymes into the intestinal lumen and exert potential synergistic (LAB) effects on digestion and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
133
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(141 citation statements)
references
References 127 publications
2
133
0
6
Order By: Relevance
“…and Clostridium sp. have been implicated in the pathogenesis of CRC (Sobhani et al, 2011) while numerous lactic acid bacterias have been shown to possess cancer-preventing attributes (Kumar et al, 2010). Wei et al (2010) also proved that Ruminococcus-like and Allobaculum-like bacteria were identified as crucial variables for discrimination of DMH-treated rats from controls.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…and Clostridium sp. have been implicated in the pathogenesis of CRC (Sobhani et al, 2011) while numerous lactic acid bacterias have been shown to possess cancer-preventing attributes (Kumar et al, 2010). Wei et al (2010) also proved that Ruminococcus-like and Allobaculum-like bacteria were identified as crucial variables for discrimination of DMH-treated rats from controls.…”
Section: Discussionmentioning
confidence: 95%
“…and Clostridium sp. have been implicated in the pathogenesis of CRC (Sobhani et al, 2011), while some lactic acid bacteria have been shown to possess cancer-preventing attributes (Kumar et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants produced by Streptococcus thermophilus are linked with decreased DNA damage, and thus, cancer by neutralizing reactive oxygen species (ROS). [18] In healthy breast, Lactococcus and Streptococcus bacteria are more prevalent because bacteria were thought to have anticancer property. Bacteria from cancerous females were grown on human breast cancer cells to check their ability of triggering DNA damage.…”
Section: Association Of Bacteria With Breast Cancermentioning
confidence: 99%
“…[16] Probiotics means "for life" or an antonym for antibiotics [17] , when taken in sufficient amount, viable and non-disease causing microorganisms (bacteria or yeasts) impart health benefits via preclusion (prevention) and cure of particular pathological disorders or can lessen the possibility of disease to host are referred as probiotics. [18,19] Various microorganisms are used as probiotics especially lactic acid bacteria (LAB). LAB includes most of Lactobacillus species, some species of Bifidobacteria, Enterococcus, and Streptococcus.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotic have been considered Generally Recognized As Safe for human consumption and known to exhibit various health beneficial effects i.e. anti-cancer, immunomodulatory, anti-oxidant, cardio protective and anti-obese/ diabetic [7][8][9]. There are various mechanisms have been proposed for the bioactivity of the probiotics on human health, and one of them is the probiotics mediated production of bioactive components during fermentation process of foods ( Figure 1).…”
mentioning
confidence: 99%